Techno-Economic Analysis of a Supercritical Gas Turbine Energy System Fueled by Methanol and Upgraded Biogas - Hossein Madi; Claude Biever; Chiara Berretta; Yashar S. Hajimolana; Tilman Schildhauer (Energies)
The HERMES project investigates the utilization of surplus wind and solar energy to produce renewable fuels such as hydrogen, methane, and methanol for seasonal storage, thereby supporting carbon neutrality and the energy transition. This initiative aims to create a closed-loop, zero-emission energy system with efficiencies of up to 65%, employing a low-pressure (≤30 bar) synthesis process—specifically, sorption-enhanced methanol synthesis—integrated into the power system. Excess renewable electricity is harnessed for chemical synthesis, beginning with electrolysis to generate hydrogen, which is then converted into methanol using CO2 sourced from a biogas plant. This methanol, biomethane, or a hybrid fuel blend powers a supercritical gas turbine, providing a flexible and reliable energy supply. Optimization analysis indicates that a combined wind and photovoltaic system can meet 62% of electricity demand, while the proposed storage system can handle over 90%. Remarkably, liquid methanol storage requires a compact 313 m3 tank, significantly smaller than storage requirements for hydrogen or methane in gas form. The project entails a total investment of 105 M EUR and annual operation and maintenance costs of 3.1 M EUR, with the levelized cost of electricity expected to decrease by 43% in the short term and 69% in the long term as future investment costs decline.